Analisis Harga, Promosi, Dan Persediaan Produk Terhadap Perpindahan Merek Rokok Lain Ke Rokok Marlboro Black Filter - Bachmid, Abdurrahman Fauzi (Universitas Sam Ratulangi, 2019)
The tobacco industry is one of the largest economic sectors in Indonesia. Many cigarette companies compete in the tobacco industry, one of them is PT. Hanjaya Mandala Sampoerna Tbk. with the product is Marlboro Black Filter. Competition between these companies results in the transfer of brands by consumers, some things that can cause brand shifts are price, promotion and product supply. The results of this study indicate that the price and inventory of products have a significant influence on the transfer of other cigarette brands to Marlboro Black Filter cigarettes. While Promotion has no significant influence on the transfer of other cigarette brands to Marlboro Black Filter cigarettesKeywords: Price, Promotion, Product Inventory, Brand Switching